Expansion of transplanted islets in mice by co-transplantation with adipose tissue-derived mesenchymal stem cells. Issue 5 (May 2018) - Tanaka, Tomoko; Kojima, Daibo; Mera, Toshiyuki; Matsumoto, Masahito; Yasunami, Yohichi; Yanase, Toshihiko
Abstract: The shortage of donor islets is a significant obstacle for widespread clinical application of pancreatic islet transplantation. To investigate whether adipose tissue-derived mesenchymal stem cells (ADSCs) induce expansion of transplanted islets, we performed co-transplantation experiments in a mouse model. Streptozotosin (STZ)-induced diabetic mice transplanted with 50 syngeneic islets remained hyperglycemic. However, hyperglycemia was ameliorated gradually when 50 islets were co-transplanted with ADSCs but not separately grafted into the contralateral kidney. Insulin and proinsulin contents of 120-day grafts containing 50 islets co-transplanted with ADSCs were significantly increased compared with those of 50 isolated islets. The Ki67-positive ratios in islets of the naïve pancreas, at 30 and 120 days grafts were 0.23%, 2.12%, and 1.52%, respectively. Ki67-positive cells were predominantly Pdx1+ and insulin+ cells. These results demonstrate that co-transplantation with ADSCs induces proliferation of transplanted islets in mice, suggesting a potential solution for the low efficiency of islet transplantation.